Chinese SWFs: meeting the dragon - Keller, Michael (Henry Stewart Talks, 2013)
China, SWFs, Sovereign Wealth Funds, Chinese investments, China Investment Corporation (CIC), SAFE Investment Company, Investment strategy, Government, State capitalism